Biodiversity and Conservation in Forests - Diana F. Tomback (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Global forest communities cover only about 30% of land areas, but they provide important ecosystem services, such as watershed protection, carbon sequestration, and oxygen production, as well as renewable forest products for human subsistence and markets. Forests also support the majority of the world$1 (Bs terrestrial biodiversity. Although land conversion for agriculture and pastureland has historically resulted in fragmentation and declining forested areas, forests worldwide are now experiencing change at an unprecedented rate due to various anthropogenic activities and growing human populations. Global warming trends are altering snowpack and hydrology, fostering outbreaks of native forest pests, and accelerating the loss of older tree age classes. Modeling suggests that future fire regimes in temperate regions will have shorter return intervals, with more severe wildfires. In addition, a by-product of trade and travel globalization has been the accelerated transport of plants and animals, and plant and animal diseases, around the world. Exotic species have altered community composition, especially where foundation tree species are affected. Every forest community worldwide is challenged by some of these problems. In this Special Issue of the journal Forests we explore the unique biodiversity supported by forest communities, how forest communities are rapidly changing, and conservation approaches to preserving forest biodiversity.s
English
Keywords: conservation; global warming; biodiversity; exotic species; restoration